Factors Related to the Performance of Officers Relating to Provision Service of National Health Care (JKN): Faktor yang Berhubungan dengan Kinerja Petugas Terkait Pemberian Jasa Pelayanan Jaminan Kesehatan Nasional (JKN) - Kismiyatul Fitriya Muftika; Mitra Mitra; Jasrida Yunita; Yanwir Kamal; Helda Suryani Munir (Jurnal Kesehatan Komunitas, 2018)
ABSTRACT In improving the service performance of health center staff, BPJS has contributed capitation fund for provision services (60%) and operational cost of Public Health Center (40%). Based on the preliminary survey, it was found that only 40% of officers with good performance, officers are still many who often come late. The purpose of this research is to know factors related to the performance of officers related to the provision service of National Health Care (JKN) at Tapung Public Health Center and Tapung II Public Health Center. With the variables studied are provision services, employment / position, attendance, work period, rewards, motivation, leadership, and demographic variables in the form of sex. This research is Quantitative research with cross sectional design was conducted from June to July of 2017. The sample in this study is all officers who received provision services amounted to 97 people. The result of this research is there is relationship of employment / position, work period, and leadership with performance, while other variables (attendance, rewards, motivation, and sex) are not related to officer performance. While service variable is variable confounding to work period. The conclusion of this research is that there is a correlation between employment / position, work period and leadership with officer performance. It is recommended that the head of Public Health Center to allocate funds outside the service for officers whose workload is more severe, motivation in the form of rewards for officers who can be exemplary, punishment for undisciplined officers, providing direction and support, and procurement of gradual evaluation and observation related to the completion of tasks by the officers.